The Effect of Mindfulness on Pain and IL-6 Level Serum ln Cancer Patient - Anisa Ell Raharyani; Yuriz Bakhtiar; Awal Prasetyo (Indonesian Journal of Global Health Research, 2023)
Pain is a common symptom experienced by patients of nasopharyngeal cancer. This pain is caused by metastasis, infection and medication. Pain can result in physical, psychological (stress), social, and spiritual impact as well as it causes the emergence of perception about death that can decrease the life quality. Pain response affects changes on psychoneuroimmunology. Integrated treatment on pain is needed. Mindfulness is one form of integrative therapy to relieve pain intensity and reduce pro-inflammatory cytokine activity as a pain response. Objective to show effect Mindfullnes on pain and Il-6 serum level in cancer patient especially nasopharyngeal cancer. Experimental clinical trial one group pre and post test design without control. Sample collected based on consecutive sampling. Pain intensity is measured by using VAS, the neutrophils count is measured by using analyzer packet and IL-6 level is measured with ELISA. The instrument validity test showed r=0.90, while the reability test showed more than 0.90. Data were analyzed using t-test. Average difference of pain intensity before therapy, (mean4,07 + 0,99), there is a difference in the pain level, neuthropyl and IL-6. Mindfulness is proved to give effect on pain intensity, neutrophils count and IL-6 level on patients with nasopharyngeal cancer.